Boundary element methods for the prediction of aircraft noise shielding in flight - Clancy, Cathal (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2011)
Aircraft noise emissions may be significantly reduced by positioning the aeroengines above the wings or fuselage so as to utilize the shielding effect of the airframe. Computational tools are likely to play a key role in the design of future low noise aircraft that maximize this shielding effect.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin